Using Theory to Inform and Guide Perinatal Bereavement Care. Issue 1 (January 2019) - Hutti, Marianne H.; Limbo, Rana
Abstract : Abstract: Providing nursing care to perinatally bereaved women and their families is difficult, emotionally demanding, and complicated. Here we demonstrate how, through understanding the theoretical underpinnings of Guided Participation and perinatal grief intensity, nurses can significantly expand their competence and confidence in their ability to provide highly individualized, supportive, relationship-based perinatal bereavement care. The way that parents respond to a perinatal loss may range from little response to highly intense, long-lasting grief. Grief after such losses may be intensified when the loss experience is highly incongruent with a parent's expectations, and the parent is unable to act to reduce this incongruence. The Hutti Perinatal Grief Intensity theoretical framework and the Perinatal Grief Intensity Scale may be used to help identify parents who are likely to experience highly intense grief and need for professional follow-up after perinatal loss. However, many parents who experience intense grief have little experience in coping with such feelings. Guided Participation is a middle-range theory of teaching and learning. It is used in the context of perinatal bereavement to help bereaved parents navigate the feelings and numerous grief-related issues that occur as a consequence of the loss, with the nurse serving as the expert guide. This combined theoretical approach to care assists nurses to assess grief intensity and to provide highly effective, relationship-driven care. Abstract : Responses of parents to miscarriage, stillbirth, and neonatal death vary dramatically, from little or no grief to highly intense, profound, and unbearable grief, especially during the first and second trimesters when meaning can vary greatly. Drs. Hutti and Limbo explain how theory can guide nursing practice in the care of parents experiencing perinatal grief and loss.